Experimental investigation of a Jet-A1 fuelled peripheral vortex reverse flow combustor. (1st March 2021) - Ahmad, Khurshid; Arghode, Vaibhav Kumar
Highlights: Strong peripheral vortex resulted in favorable combustion and emission behavior. Fuel jet retraction significantly improved the atomization of coaxially injected liquid fuel. Reaction zone is stabilized further downstream in non-premixed mode vs. prevaporized-premixed mode. Low NOx and CO emissions were demonstrated in non-premixed mode using Jet-A1 fuel. Abstract: Combustion characteristics of a novel peripheral vortex reverse flow (PVRF) combustor are investigated using Jet-A1 fuel. Previously, we have demonstrated the operation of PVRF combustor using LPG and ethanol fuels, and here we demonstrate and investigate the operation of PVRF combustor using Jet-A1 fuel . The combustor was operated at atmospheric pressure with preheated inlet air (300 °C) and high thermal intensity (25 MW/m 3 -atm at ø = 0.8) relevant to gas turbine combustors. Conventional swirler was not employed and the reactants were injected as jets. Combustion was primarily stabilized due to a dominant peripheral vortex of hot burned gases inside the combustor. In the non-premixed mode, the liquid fuel was injected coaxially w.r.t. the incoming air-jet and it was atomized due to strong shearing from the annular air jet. Shadowgraphy was used to investigate the atomization characteristics of the fuel. Electrochemical gas analyser was used to measure exhaust emissions (NOx, CO). The combustor demonstrated low emissions and stable operation over a wide range of equivalence ratios. CH* chemiluminescence was used to study the location and the dynamic behaviour of the reaction zone. The reaction zone was positioned further downstream in the non-premixed mode as compared to the prevaporized-premixed mode suggesting that atomization, evaporation and mixing of fuel in the non-premixed mode is causing a delay for the onset of the reactions. From shadowgraphy images, it was observed that retraction of the fuel jet considerably improved the fuel atomization.